1975
DOI: 10.1111/j.1365-2427.1975.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal stratification, photosynthesis and nitrogenfixation in a shallow, equatorial Lake (Lake George, Uganda)

Abstract: From a series of experiments and measurements covering one 24-h period in LakeGeorge the diurnal patterns of photosynthesis, nitrogen-fixation and stratification are described. The thermal cycle shows three distinct phases of isothermy, intense stratification and mixing. During stratification the surface water temperature reached 36°C, whereas the bottom temperature remained at 25°C. The phytoplankton are evenly distributed at dawn, sink out during the day and tend towards an even redistribution as thermal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1
3

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 39 publications
5
42
1
3
Order By: Relevance
“…For instance, recalculating from the data of , Clear Lake (California) produced 121 mg N m 2 day 1 on one occasion, but the annual mean was apparently about 5 mgN nr 2 day'. Ashton (1981) found up to 47.94 mgNm -day ', depending on conditions, in a South African impoundment, and Ganf & Home (1975) found 58 mgNm ~2day~', in comparable experimental conditions to ours, for Lake George (Uganda). These results were for plankton in eutrophic lakes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For instance, recalculating from the data of , Clear Lake (California) produced 121 mg N m 2 day 1 on one occasion, but the annual mean was apparently about 5 mgN nr 2 day'. Ashton (1981) found up to 47.94 mgNm -day ', depending on conditions, in a South African impoundment, and Ganf & Home (1975) found 58 mgNm ~2day~', in comparable experimental conditions to ours, for Lake George (Uganda). These results were for plankton in eutrophic lakes.…”
Section: Discussionsupporting
confidence: 84%
“…Of all these studies only that of Ganf & Home (1975) includes any details of light through the water column, and even in this instance they were analysed only with respect to photosynthesis, although the N 2 -fixation was related to photosynthesis. The predictive power of the light field has therefore been given scant attention by most workers, though the use of heterocyst numbers, and to some extent nutrients, in this regard has not been missed, e.g., , and in most other studies where heterocysts have been counted.…”
Section: Discussionmentioning
confidence: 99%
“…5). While lakes in the present study had little DO variation at scales ranging from about 8 to 15 h, others have found significant variability in tropical, shallow lakes (Ganf & Horne 1975). It would be interesting to conduct a similar study in tropical lakes where different controls of O 2 dynamics may operate.…”
Section: Temperaturementioning
confidence: 60%
“…The higher daily rates recorded for Pyramid Lake in 1979 were 3-5 mmol CzH4 m-2 d-l during the bloom period, similar to values of l-l 4 mmol C2H4 mm2 d-l found for shallow, warm eutrophic lakes (Horne and Viner 197 1;Ganf and Horne 1975). Some values for the Baltic Sea are much lower: 6-80 bmol m-2 d-l (Rinne et al 198 1).…”
Section: Discussionmentioning
confidence: 55%